Porque nos revemos nos outros Primatas? A Antropologia Biológica elucida-nos - Minhós, Tânia (Trabalhos de Antropologia e Etnologia, 2020)
Non-human primates are our closest relatives and we share with them several traits and evolutionary trends. For example, we all have an opposable thumb, large and well-developed eyes, large brains and very slow development, with the progeny highly dependent on the mother for long periods of time. Because of this evolutionary proximity, the field of Primatology is one of the disciplines included in Biological Anthropology that aims to understand human evolution and adaptation. The well-recognized primate intelligence had a crucial role shaping the human evolutionary path, thus being one of the main research areas in Biological Anthropology. Ecological and social challenges posed by the environment may have act as the evolutionary engine to the development of the complex cognitive capacities of this well succeeded taxonomic group. Therefore, understanding the socio-ecological diversity of primate societies and its determinants is crucial to better understand human evolution.